IMPLEMENTASI 'GORENG LUNJAR' DALAM INTERNALISASI KARAKTER GOTONG ROYONG PADA SISWA LAMBAN BELAJAR DI SEKOLAH DASAR - Ratnaningsih; Wildan Nurul Fajar (STKIP Subang, 2026)
This study examines the design, implementation, obstacles, and impact of the GORENG LUNJAR model (Gotong Royong Ekspresif dan Ramah Siswa Lamban Belajar/Expressive and Inclusive Cooperative Learning for Slow Learners) in internalizing the value of gotong royong (mutual cooperation) among slow learner students at Grade 6B SD Negeri Patimuan 01. The model was developed in response to three identified root problems: a one-size-fits-all character education approach that excluded slow learners from meaningful participation, the absence of differentiated character activity design, and the lack of a structured peer tutoring system. This study employed a qualitative descriptive approach with a single case study design. Data were collected through direct classroom observation, peer tutor reflection journals, student emoji journals, teacher anecdotal records, and parent communication via liaison books. Data analysis followed the Miles, Huberman, and Saldaña model, comprising data reduction, data presentation, and conclusion drawing. The findings indicate that the GORENG LUNJAR model, which utilizes tiered cooperative tasks, structured peer tutoring, and emoji-based reflective journals as an inclusive communication tool, successfully shifted slow learner students from active refusal and reluctance toward repeated willingness to participate in cooperative activities. Changes also occurred in peer tutors who developed empathy and self-management skills, and in the overall classroom culture which shifted from individualistic and stigmatizing toward collaborative and inclusive. The study highlights that character internalization among slow learners requires differentiated design, effort-oriented appreciation, and structured accompaniment rather than uniform instruction.